Climate change risks in electricity networks. Issue 2 (June 2015) - Blake, Simon; Davison, Peter; Greenwood, David; Wade, Neal
Abstract : Climate change as forecast by UKCP09 will affect the planning and operation of power transmission and distribution systems in Great Britain. The links between climate change and networks are identified. The risk of flooding is very likely to increase, with the greatest effect if substations are inundated. The optimal size and location of electricity transmission corridors is difficult to define because of uncertainty in the seasonal, regional and absolute changes to wind-speed and corresponding wind generation. Although equipment in Great Britain is already fundamentally designed to operate in the future conditions anticipated under climate change, marginal changes to the capabilities of equipment will need to be accounted for in parameters used in network planning procedures. The indirect effect of climate change, created by the political response designed to minimise greenhouse gas emissions, will be more significant than the direct impact of a changing climate. This will dramatically change the generation mix, overall demand and both seasonal and diurnal demand profiles. An industry with a wider range of tools and technical solutions for planning and operation will be more prepared to manage capacity, stability and reliability at lower cost than if present methods do not evolve.